Theorizing multiculturalism : a guide to the current debate - Willett, Cynthia (Blackwell, 1998., 1998)
This wide-ranging anthology of classic and newly commissioned essays provides an essential resource - the very first collection of the major theories of multiculturalism from a multiplicity of philosophical perspectives. Essays span the major positions, including Post-Hegelian Theories of Recognition, Post-Marxism, Postcolonialism and Ethnicity, Liberalism, Analytic and Continental Feminism, Pragmatism,